Fiscal Multipliers for Brazil - Matheson, Troy (IMF Working Papers; Working Paper, 2016)
We find historical fiscal multipliers for Brazil around 0.5, larger than what existing literature typically identifies for the average emerging market. However, spending and public credit multipliers seem to have dropped to near zero since the global financial crisis, as the estimate for the whole sample period (1999-2014) is about 1\2 of that for precrisis years. By contrast, revenue multipliers have remained broadly stable. We conclude that fiscal consolidations based on expenditure and public credit retrenchment are likely to entail a modest drag on growth in the near term.